Direitos humanos e narrativa: reflexões paradoxais sobre a paz - Pena, Adriana Francisca Souza (2014)
The present work has the aims to bring to light evidences that the relationship between the dominant nation-states, dominated nation-states and human rights is today presented in a distorted way: the sovereign entity that was created to protect the interests of nations, in practice, when acts, does so as an agent of coercion. The situation is that we live in a state of emergency, a state of war in which the military and economic power dominates the world of fear. Using the writings of Walter Benjamin and his notion of Erfahrung (crossing) as well as the critique of mythologem of sovereignty and social contract theory we intend to show the need for behavioral change through education for peace with the aim of forming a culture of peace and not an institutional program that will regulate the war, as occurred with the production of peace treaties and institutions created from them, especially in the period of World War II